GOVERNANCE REFORM IN THE ERA OF DECENTRALISATION: A COMPARISON OF THE ROLES OF SMART GOVERNANCE, GOOD GOVERNANCE, AND HUMAN RESOURCE CAPACITY IN ADDRESSING CORRUPTION - Aruni, Fidhia; Taufiqurokhman; Satispi, Evi; Andriansyah; Firmansyah, Yasef (Moestopo International Review on Social, Humanities, and Sciences, 2025)
This study comprehensively examines governance reform in the era of decentralisation, focusing on comparing the roles of Smart Governance, Good Governance, and Human Resource (HR) capacity in corruption mitigation efforts. Using a literature review approach, this article analyses various concepts, theories, and empirical findings related to the implementation of these three pillars of governance in the context of dynamic decentralisation. The results of the study show that Good Governance provides an essential foundation of ethics, transparency, and accountability, forming a normative framework for clean governance. Meanwhile, Smart Governance complements this with technological innovation, big data utilisation, and digital solutions to improve the efficiency of public services, accelerate decision-making, and narrow the gap for corruption. Human resource capacity, in terms of technical and managerial competence as well as moral integrity, has proven to be a crucial factor in bridging governance principles with practical implementation in the field. This study concludes that a synergistic combination of Good Governance as a foundation, Smart Governance as an accelerator, and competent human resources as implementers, supported by strong regulations and active public participation, is key to creating a robust and effective governance system to address the challenges of corruption in the era of decentralisation. This research has important implications for the formulation of integrated anti-corruption policies and strategies at the local and national levels.